Asynchronous Motors with Electromechanical Brakes - V. V. Solencov; V. V. Brel (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
The paper contains analysis of widespread designs of asynchronous motors with electromechanical brakes. The requirements imposed on these brakes are given in the paper. The paper presents conclusions on prospects of designing such motors.